The Future of Banking in CESEE after the Financial Crisis - Ernest Gnan; Andras Simor; Manfred Schepers; Markus Eller; Michael Froemmel; Nora Srzentic; Debora Revoltella; Fabio Mucci; Malgorzata Iwanicz-Drozdowska; Petra Kalfmann (SUERF - The European Money and Finance Forum, 2011)
On 23 June 2010, the Magyar Nemzeti Bank and SUERF jointly organised a conference on "The Future of Banking in CESEE after the Financial Crisis", incorporating the SUERF Annual Lecture, delivered by Manfred Schepers, Vice President, Finance at the European Bank for Reconstruction and Development, on "The role of domestic financial markets in an integrated Europe". This SUERF Study compiles selected papers presented at this conference. To capture a full picture of the information and views collected at the conference, the introduction also summarises findings from presentations given orally at the conference only.
Keywords: C3; E4; E5; F3; G2; 330; Financial stability; external funding; macroprudential supervision; lending; fiscal policy; Regulatory reform; fiscal consolidation; cross-border banking; bank financing; Bank lending to the private sector; transition economies; credit growth; financial crisis; Convergence; consumption; investment; efficiency; profitability; Deposit insurance (guarantee); coverage; moral hazard; payout capability; Risk management; governance; corporate business; project finance; Finanzkrise; Finanzmarktregulierung; Regulierung; Bankgeschäft; Bankrisiko; Einlagensicherung; Osteuropa; Südosteuropa